2015
DOI: 10.1038/srep15140
|View full text |Cite
|
Sign up to set email alerts
|

Homophyly/Kinship Model: Naturally Evolving Networks

Abstract: It has been a challenge to understand the formation and roles of social groups or natural communities in the evolution of species, societies and real world networks. Here, we propose the hypothesis that homophyly/kinship is the intrinsic mechanism of natural communities, introduce the notion of the affinity exponent and propose the homophyly/kinship model of networks. We demonstrate that the networks of our model satisfy a number of topological, probabilistic and combinatorial properties and, in particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…This is the reason why there is always an outside condition governing the algorithms of modularity maximisation. Our experiments in [31], [32], and [36] also showed that in most cases, the algorithms of modularity maximisation fail to detect natural communities (or ground-truth communities) of real world networks.…”
Section: Basic Theoremsmentioning
confidence: 72%
See 4 more Smart Citations
“…This is the reason why there is always an outside condition governing the algorithms of modularity maximisation. Our experiments in [31], [32], and [36] also showed that in most cases, the algorithms of modularity maximisation fail to detect natural communities (or ground-truth communities) of real world networks.…”
Section: Basic Theoremsmentioning
confidence: 72%
“…and b) creates d edges from v to nodes of the same colour in G i−1 , chosen with a probability proportional to the degrees in G i−1 . It has been shown [31] that the networks generated by the homophyly/kinship model truthfully reflects many real networks, including both biological networks and social networks. We have also demonstrated that the homophyly/kinship model provides a methodology for community analyses of networks [31].…”
Section: ) (Homophyly/kinship) Otherwise Then V Chooses An Oldmentioning
confidence: 98%
See 3 more Smart Citations